2005
DOI: 10.1002/app.21391
|View full text |Cite
|
Sign up to set email alerts
|

Water‐soluble polymers and gels from the polycondensation between cyclodextrins and poly(carboxylic acid)s: A study of the preparation parameters

Abstract: Native cyclodextrins (CDx) and some of their derivatives were reacted with poly(carboxylic acid)s (PCAs) [citric acid (CTR), 1,2,3,4-butanetetracarboxylic acid (BTCA), and poly(acrylic acid) (PAA)]. These reactions were carried out in the dry state at a temperature greater than 140°C in air or in vacuo. They resulted in water-soluble and insoluble polymers formed by polyesterification between CDx and PCA. In this study, the parameters of the reaction were studied, and their influence on the water solubility or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 18 publications
(16 reference statements)
1
104
0
1
Order By: Relevance
“…The CTR being a triacid, residual COOH are present in the three-dimensional network at the end of the reaction. Previous works showed that the esterification occurs from 130°C [11]. A constant temperature of 130±1°C was applied for all this study.…”
Section: 2mentioning
confidence: 99%
“…The CTR being a triacid, residual COOH are present in the three-dimensional network at the end of the reaction. Previous works showed that the esterification occurs from 130°C [11]. A constant temperature of 130±1°C was applied for all this study.…”
Section: 2mentioning
confidence: 99%
“…The chemical reaction cannot occur between cyclodextrin (CD)/citric acid (CTR) and PET nanofibers directly, since PET, a polymer based on terephtalic acid and ethylene glycol, does not contain free reactive groups. Therefore, we modified the surface of the electrospun PET nanofibers through the polymerization reaction between CTR and CD [21,24,25]. Water-insoluble cyclodextrin polymer (CDP) network was formed by the crosslinking reaction between CD and CTR [26].…”
Section: The Cdp Formation Onto Electrospun Pet Nanofibersmentioning
confidence: 99%
“…Initially, electrospun PET nanofibrous mats were impregnated in a solution of CD, CTR, and sodium hypophosphite (SHPI, catalyst), and then dried, followed by curing at 180 • C for 7 min. CTR turn into a cyclic anhydride intermediate by thermal dehydration at elevated temperature, and then hydroxyl groups of CD reacted with the carboxyl groups of citric acid [25]. The mechanism of the CDP formation is schematically described in Fig.…”
Section: The Cdp Formation Onto Electrospun Pet Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent polymer networks containing cyclodextrins are of great interest because their croslinked macromolecular structure has a cooperative action between the cyclodextrin cavities, or between the cavities and the polymeric network, in the complexation and adsorption of water soluble components. From this perspective, CD polymers were prepared by solubilization of citric acid as crosslinking agent and sodium hypophosphite as catalyst [17,18], and they were used to improve the complexation of some drugs. These polymers with an anionic character present low toxicity and an environmentally friendly composition.…”
Section: Network Of Polymers and Cyclodextrinsmentioning
confidence: 99%